Alienasi Pekerja Pada Masyarakat Kapitalis Menurut Karl Marx - Datu Hendrawan (Arete, 2017)
Marx and Marxism are often identified with evil movements that threaten the safety of mankind. Yet when examined, the point depart from Marx’s thinking also comes from humanitarian problems. Karl Marx formulated the basis of his humanity through a quite unique way. Karl Marx does not justify what is humanity (universal), but he reveals the phenomenon of degeneration of humanity through the concept of work alienation. Karl Marx’s struggle with the idea of alienation while in France. The concept of alienation was formulated by Marx in his encounter with Engels’s idea of the suffering of workers in Europe. The concept of alienation is the basis for the theory of class struggle to be formulated later. The awareness of human oppression which is demonstrated through its alienation produces a theory that has the purpose of praxis. Awareness of oppressive circumstances is expected to drive changes to the political and economic system. Work to make workers experience alienation. In a working condition, a worker is actually alienated from his production. When alienated from the production of a worker also do a job that is foreign and not in accordance with the purpose of life. Furthermore, the working conditions to make humans alienated from humanity, because work is no longer an autonomous self-disclosure but only aims to meet the needs of life (animal). The state of the alien world of work makes the workers alienated from the social world. Other workers are foreigners who are placed as opposed to the outsourced workers. Work also makes people alienated from themselves, because the body does not do something that suits the mind.